Teachers’ Perspectives on CLIL Implementation in Indonesian Primary Schools: Challenges and Classroom Strategies - Oky Adinda Putri; Fatiha Dyah Puspa Ardianti Puspa Ardianti; Laili Febriyanti; Diah Kurniati; Titis Sulistyowati (Prominent, 2025)
This study explores teachers’ perspectives on the implementation of Content and Language Integrated Learning (CLIL) in science and math classrooms at SD Al Azhar Pati, a primary school in Indonesia. While CLIL is acknowledged as a bilingual instructional strategy that enhances both language and subject knowledge, limited research has explored its implementation in non-international, resource-limited school contexts. Using a qualitative case study approach, data were collected from five teachers through structured questionnaires and semi-structured interviews via WhatsApp. Findings reveal that teachers view CLIL as effective for fostering academic vocabulary and meaningful learning. However, challenges such as language barriers, limited materials, and varied student engagement persist. Teachers employed bilingual strategies, interactive activities, and collaboration with English teachers to overcome these challenges. This study underscores the need for professional development and localized resources to strengthen CLIL practices in similar settings.